Potency of Indonesian natural products for nutraceutical, pharmaceutical and cosmeceutical industry development. - Rukayadi, Yaya (2012)
Indonesia is a tropical country and the largest archipelago in the world. Its wide range of natural habitats, rich plant and animal resources and high numbers of island endemics, Indonesia is recognized as a major world centre for biodiversity. Biological diversity is more than just the sum of species numbers. It encompasses the variety, variability and uniqueness of genes, species and the ecosystems where they occur. Therefore this country is rich of tropical natural resources which can be developed as various nutraceutical, pharmaceutical and cosmeceutical industry. Indonesia is recognized as one of major centre in the world for the tropical medicinal plants resources which it’s various potentials for medicine and beauty. It is estimated that there are about 2,500,000 species of higher plants; the majority of these have not been examined in detail for their pharmacological and cosmeceutical activities. The use of plant extracts in pharmaceutical and beauty products formulation is also on the rise. Thus, a renewed interest of beauty functions derived from medicinal plants has emerged over the past decade. Indonesia has also a dense population with multi-ethnic groups which will create various culinary cultures and eating habits. Since long time ago, some Indonesian indigenous food is well known for its potencies to prevent diseases and to maintain healthy condition beside to fulfil the nutrition requirements. In relation with food diversity which differs on each kind of food ingredients, Indonesia has lots of food ingredients that can give physiologically active potencies to be further developed as functional food or nutraceutical.